COMPUTATIONAL MODELING OF HEAVY DUTY TRUCK DRIVESHAFT (Perner’s Contacts, 2016)
The driveline of heavy duty vehicle is an important source of NVH. Prediction of NVH parameters of driveline in construction phase is a significant topic nowadays because it can save time and development costs, but requires more complex mathematical models. This paper describes the use of MBS simulation tool for prediction of driveshaft vibration where shaft is modeled as a flexible body. MBS approach can take into account various input parameters, i.e. unbalanced mass of shaft, geometry deviation from ideal shape, mounting points of eccentricity or contact between the shaft and other parts of the driveline. MBS model of driveshaft was verified by measurement on a real vehicle.